Optimization of minibeam generation by mechanical collimation in proton minibeam radiation therapy. (September 2016) - Guardiola, C.; Peucelle, C.; Prezado, Y.
Abstract : Introduction: The dose tolerances of normal tissues continue being the main barrier in radiotherapy. To lower it, we recently proposed a novel concept: proton minibeam radiation therapy (pMBRT). It allies the inherent advantages of protons with the normal tissue preservation observed when irradiated with submillimetric spatially fractionated beams. The tumor receives a homogeneous dose distribution, while normal tissues benefit from the spatial fractionation of the dose. Purpose: We have recently implemented this technique at the Orsay proton therapy clinical center. This work aims at optimizing the minibeam generation by means of a mechanical collimation. Materials and methods: Monte Carlo simulations (GATEv7.1) were used to evaluate different irradiation configurations, e.g. collimator dimensions and materials (Brass, Tungsten, Iron and Nickel). Clinically relevant energies were used. Neutron contamination, Peak-to-valley dose ratios (PVDR) and beam penumbras were used as figures-of-merit. Results: The neutron dose due to the minibeam collimator was found to be lower than 0.002% of the primary dose. A tungsten collimator provides the higher PVDR, but the generated neutron yield is 3 times higher than in other materials. Brass seems to provide the best compromise between PVDR values and neutron contamination. Conclusion: A mechanical collimation only increases the biologic neutron dose by 0.04% of the peak surface dose therefore it is suitable for pMBRT. An optimized collimation for pMBRT, providing the best compromise between a high PVDR and low neutron generation, has been obtained.